The Influence of Financial Literacy and Lifestyle on Use of Fintech Payment For Students University Faculty of Social Sciences Universitas Pembangunan Panca Budi - Tarima Nurhayati Pangaribuan; Syahrial Hasanuddin Pohan (Penerbit Jurnal Indonesia, 2025)
The development of digital financial technology in payments has changed the behavior of financial transactions, especially among the younger generation. This study aims to find out and analyze the influence of Financial Literacy and Lifestyle on the use of fintech payment in students of the Faculty of Social Sciences, Panca Budi Development University. This type of research is an associative research with a quantitative approach, using questionnaires as a data collection tool. The sample in this study consisted of 70 students majoring in Management at Panca Budi Development University, which was determined using slovin calculations. For data analysis, multiple linear regression was used with the help of SPSS software version 23. The results of the study show that partially, Financial Literacy does not affect the use of Fintech Payment, while Lifestyle has a significant positive influence on the use of Fintech Payment. Simultaneously, Financial Literacy and Lifestyle have a positive and significant influence on the use of Fintech Payment for Management Students at Panca Budi Development University. This research model is able to explain 29.7% of the variations in the use of fintech payments.